METHODS AND MEANS OF DEVELOPING MUSICAL TASTE IN FUTURE MUSIC TEACHERS THROUGH INSTRUMENTAL PERFORMANCE - Nurmatov Hoshimjon Nemat oglu, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Annotation: This article analyzes the issues of developing musical taste in future music teachers through instrumental performance. It reveals the importance of classes organized on the basis of analytical, creative, and reflective approaches in the process of improving musical taste. The results of experimental studies demonstrate the positive impact of instrumental performance on the development of musical perception, artistic thinking, and aesthetic evaluation skills.